Forehead carbuncle with intractable headache - Chou, Ping-yin (Neuropsychiatr Dis Treat, 2015)
Although carbuncles are commonly seen and may heal on their own or respond well to treatment, in rare conditions, bacteria from carbuncles can spread into the bloodstream and migrate to other areas of the body. Herein, we report on an elderly female who suffered from forehead carbuncle with intractable headache, later confirmed as having subgaleal abscess. Physicians should pay special attention to elderly and immune-compromised patients with carbuncles located on the middle of the face, especially when accompanied by intractable headache, to avoid poor outcome.